Exchangeable and Total Body Potassium in Patients with Chronic Renal Failure. Issue 5793 (15th January 1972) - Boddy, Keith; King, Priscilla C.; Lindsay, R. M.; Winchester, J.; Kennedy, A. C.
Abstract : Total body potassium determined by whole-body monitoring and exchangeable body potassium estimated with 43 K were measured simultaneously in 12 patients with stable chronic renal failure. Values for the exchangeable potassium were obtained after equilibration periods of 24, 48, and 64 hours. The exchangeable body potassium, expressed as a percentage of the total body potassium (mean ± S.E. of mean), gave values of 60·7 ± 3·3%, 83·6 ± 2·7%, and 85·9 ± 2·7% at 24, 48, and 64 hours respectively. It seems that the equilibration between radioactive and native potassium is incomplete after 24 hours; and that exchangeable potassium measured at this time is not an accurate index of the status of total body potassium in such patients. Furthermore, the finding that the value at 64 hours is significantly less than found in healthy subjects suggests that the exchangeable potassium is a smaller fraction of the total body potassium in patients with chronic renal failure.